A Review on Macrophage Activation Syndrome - Preeti Sharma; Shailza Shreshtha; Pradeep Kumar; Rachna Sharma; T.K. Mahapatra (Journal of Pure and Applied Microbiology, 2019)
MAS, which is currently grouped under secondary or acquired haemophagocytic lymphohistiocytosis (sHLH), is a rare and fatal disorder that results from excess activation of T-cells and macrophages. Though the pathogenesis of MAS is poorly understood, various proinflammatory cytokines like interleukins (IL-1, IL-6), tumor necrosis factor α (TNF α), interferons are thought to play significant roles. MAS is associated with various clinical features such as non-remitting fever, bleeding, cytopenias, splenomegaly, hepatic dysfunctions, increased levels of triglyceride, ferritin and decreased levels of albumin and fibrinogen. Early diagnosis and interventions are crucial to reduce mortality risk but diagnosis is not often easy due to persistence of wide range of features that overlap with other rheumatic diseases, most commonly sJIA (systemic juvenile idiopathic arthritis). Corticosteroids and cyclosporins are commonly used for MAS treatment. Intravenous immunoglobulins, biologic agents like IL-1 blockers (anakinra, canakinumab), IL-6 blockers (tocilizumab) are also frequently used. Moreover there is still the need of genetic and immunohistological study in order to understand the exact mechanism of the syndrome development and establishment of novel therapies with lesser toxicities.